One model of optimal resource allocation in homogeneous multiprocessor system - Doroshenko, A.Yu.; Ignatenko, O.P.; Ivanenko, P.A. (PROBLEMS IN PROGRAMMING, 2025)
This paper deals with the control model of optimal recourse allocation in homogeneous multiprocessor system. We proposed an approach to developing optimal control using fluid models theory domain. We obtain analytic solution for time depending of parallel execution parameters. Results are validated by experimentation for matrix multiplication example.Problems in programming 2011; 1: 29-38